From Thia- to selenadiazoles: changing interaction priority - Lindner, Benjamin; Coombs, Benjamin A.; Schaffroth, Manuel; Engelhart, Jens U.; Tverskoy, Olena; Rominger, Frank; Hamburger, Manuel; Bunz, Uwe H. F. (Organic letters, 2013)
The synthesis, optical, and electrochemical properties as well as solid-state structures of a series of alkynylated, benzannulated selenadiazoles are reported. This set of compounds is compared to the lighter homologue series, the thiadiazoles. The selenadiazoles show head-to-head dimerization in the solid state, while packing of the thiadiazoles was dominated by the steric bulk of the side groups. The Se-N interaction is a supramolecular motif that should drive the effective self-assembly and modulate charge transport when these compounds are used as thin films in devices.